Innovation in Energy Law and Technology: Dynamic Solutions for Energy Transitions - Pols, Auke (Prometheus (Saint Lucia, Brisbane, Qld.), 2020)
Pols reviews Innovation in Energy Law and Technology: Dynamic Solutions for Energy Transitions edited by Donald Zillman, Martha Roggenkamp, Leroy Paddock and Lee Godden.